2022
DOI: 10.1002/jor.25253
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate treatment suppresses osteoblastic differentiation by inducing Notch2 signaling and blockade of Notch2 rescues osteogenesis by preserving Wnt/β‐catenin signaling

Abstract: Methotrexate (MTX) is a commonly used antimetabolite in cancer treatment. Its intensive use is linked with skeletal adverse effects such as reduced bone formation and bone loss, and yet little information is available on molecular mechanisms underlying MTX‐induced impaired bone formation. This study investigated the effects of MTX treatment at a clinical chemotherapy relevant dose on osteogenic differentiation in MC3T3E1 osteoblastic cells. To investigate the potential mechanisms, the expression of 87 genes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…To examine the potential direct role of Notch2/Hey1 pathway in endothelial cell dysfunction, we conducted in vitro studies assessing treatment effects with MTX ± anti-Notch2 antibody in cultured rat bone marrow-derived endothelial cells (BMECs). Our results demonstrated that MTX exposure at a clinical chemotherapy relevant dose (10µM) [ 17 , 43 , 44 ] induced Notch2 activation with significantly increased mRNA expression levels of Notch ligand Jag1, Notch2 receptor, and Notch target gene Hey1 in cultured cells, and that supplementation of anti-Notch2 antibody suppressed MTX-induced Hey1 induction. Previously, over-expression of Hey1 was shown to inhibit proliferation, tube formation and migration in human endothelial cells [ 81 ].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…To examine the potential direct role of Notch2/Hey1 pathway in endothelial cell dysfunction, we conducted in vitro studies assessing treatment effects with MTX ± anti-Notch2 antibody in cultured rat bone marrow-derived endothelial cells (BMECs). Our results demonstrated that MTX exposure at a clinical chemotherapy relevant dose (10µM) [ 17 , 43 , 44 ] induced Notch2 activation with significantly increased mRNA expression levels of Notch ligand Jag1, Notch2 receptor, and Notch target gene Hey1 in cultured cells, and that supplementation of anti-Notch2 antibody suppressed MTX-induced Hey1 induction. Previously, over-expression of Hey1 was shown to inhibit proliferation, tube formation and migration in human endothelial cells [ 81 ].…”
Section: Discussionmentioning
confidence: 78%
“…To investigate the possible role of anti-Notch2 (NRR2) antibody in protecting endothelial cells against MTX damage, cells (at reaching 70% confluency) were treated with saline or MTX (10 µM) along with either the anti-ragweed antibody as control IgG (10 µg mL −1 ) or the anti-Notch2 antibody (10 µg mL −1 ) for 24 h, after which time the cells were harvested and conditioned medium was collected. The selected dose for MTX treatment in vitro is the chemotherapy relevant dose for MTX in cell culture studies [ 17 , 43 , 44 ]. The dose chosen for anti-Notch2 antibody treatment has previously been used in different in vitro studies to block Notch2 receptor activity effectively [ 36 , 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it has been illustrated that Notch2 induces osteoclastogenesis via enhancing expression of nuclear factor of activated T-cells 1 (NFATc1) [41]. Recently, in an in vitro study, we have found that MTX treatment-suppressed osteoblastic differentiation was associated with induced Notch2 signalling and Notch2 blockade attenuated MTX adverse effect in osteogenesis by activating Wnt/β-catenin signalling [42]. Despite previous studies on roles of Notch2 in skeletal development and diseases, there is a lack of knowledge about the potential roles of Notch2 signalling in cancer chemotherapy-induced bone defects.…”
Section: Introductionmentioning
confidence: 99%